Duration of parental leave and women's employment - Kim, Jungho (Seoul Journal of Economics, 2020)
The study examines the consequence of the extension of maximum job-protected and paid leave from 12 months to 15 months in Korea. The analysis, based on regression discontinuity design, finds the reform led to more female employees taking leave and for longer periods. The take-up of leave increased by five percentage points and the duration by 40 days. The probability of returning to work within three years after birth increased by two percentage points after the policy change, but the effect diminished by four years after birth. No significant impact on their return to their pre-birth job is found. This finding implies that a relatively small change in parental leave legislation may promote women's employment in the short-term. Moreover, the extension of the maximum duration of job-protected leave is not enough to support women's career development in the long-term. Finally, the shortterm impact on women's employment was the largest for those with the lowest wage and in the smallest firms. Although the evidence is not definitive, the heterogeneous effect needs to be paid further attention in evaluating parental leave policy.
Keywords: Female labor supply; Natural experiment; Parental leave; Timing of childbearing